Efficacy and safety of iota-carrageenan nasal spray versus placebo in early treatment of the common cold in adults: the ICICC trial - Eccles, R. (Respir Res, 2015)
ABSTRACT: Iota-carrageenan (I-C) is active against respiratory viruses in vitro and was effective as nasal spray in three previous clinical trials. The current trial served to further investigate I-C in patients with early common cold symptoms. METHODS: This randomized, placebo-controlled, double-blind phase IV trial was conducted in 200 adult patients with self-diagnosed colds of <48 h’ duration that were confirmed by baseline cold symptom scores. Patients were to self-administer 0.12 % I-C or placebo spray (NaCl 0.5 %) four times daily for four to ten days and record symptom information for ten days. Common respiratory viruses were quantified by RT-PCR during pretreatment and on Day 3 or 4. The primary endpoint was the mean total symptom score (TSS) of eight cold symptoms on Days 2–4 (TSS(2–4)). RESULTS: Patients in both treatment groups had similar baseline TSSs (mean TSS: 6.75 for I-C and 6.79 for placebo). Viruses were detected in baseline samples from 53 of 98 I-C patients (54.1 %) and 54 of 97 placebo patients (55.7 %). Mean ± SE for TSS(2–4) was 5.78 ± 0.25 for I-C patients and 6.39 ± 0.25 for placebo (p = 0.0895). Exploratory analyses after unblinding (TSS(2–4) excluding a patient with aberrantly high symptom scores [TSS(2–4, ex 1pt)]; mean of TSS over Days 1–4 [TSS(1–4)]; change in TSS(1–4) relative to baseline [TSS(1–4, rel)]) demonstrated treatment differences in favor of I-C (p = 0.0364, p = 0.0495 and p = 0.0421, respectively). For patients with quantifiable rhinovirus/enterovirus at baseline, there was a trend towards greater reduction of virus load at Day 3 or 4 (p = 0.0958; I-C: 90.2 % reduction in viral load; placebo: 72.0 %). Treatments were well tolerated with no differences in adverse event rates. CONCLUSIONS: The primary endpoint did not demonstrate a statistically significant difference between I-C and placebo but showed a trend towards I-C benefit. Exploratory analyses indicated significant reduction of cold symptoms in the I-C group relative to placebo during the first four days when symptoms were most severe, and also substantiated I-C’s activity against rhinovirus/enterovirus. TRIAL REGISTRATION: NCT01944631 (clinicaltrials.gov)